"Never Abandon, Never Give Up": Soldiers Sortie as a New Red Classic of the Reform Era. Issue 1 (19th June 2019) - Zhang, Zhen
Abstract : At the height of the socialist era, China produced decidedly influential revolutionary subjects, generating a legacy that is a source of vibrant cultural production in the reform era. This article explains the success of the popular TV drama series Soldiers Sortie (Shibing tuji, 2007) by contextualizing its reworking of core social values through re-fashioning socialist heroic subjects. This revision conjoins the collectivism of a socialist past with the individualism of a capitalist economy in order to promote a new Chinese identity. This adaptation of Chinese personhood keeps the revolutionary spirit alive by erasing historical specificity in order to develop group and individual identity without neglecting the reality of incomplete revolution and uneven development in China.